Competitive Game Play Attenuates Self-Other Integration during Joint Task Performance - Ruissen, Margit I.; de Bruijn, Ellen R. A. (Frontiers in Psychology, 2016)
Joint task performance is facilitated by sharing and integrating each other’s action representations. Research has shown that the amount of this so-called self-other integration depends on situational aspects related to the social context, including differences in the social relationship between co-acting individuals. There are indications that a cooperative relationship facilitates self-other integration while a competitive relationship results in more individualistic task performance. However, findings from previous studies in which the cooperative or competitive element was manipulated during task performance are inconsistent. Therefore, the present study aimed to manipulate the social relationship between two individuals prior to performing a social Simon task. This task is frequently used to measure self-other integration and distinction processes. A mixed-within-and-between-subjects design was used in which three groups of participants performed both a standard Simon task and a social Simon task after having played a Tetris game either individually, in cooperation with a co-actor, or in competition against another participant. Performance on the standard Simon task was not affected by the Tetris manipulation. However, a sustained effect of the induced cooperative versus competitive relationship was found on the social Simon Task. Less self-other integration was found in participants who had first played a competitive Tetris game compared to participants who had played a cooperative or solo version of the game. The current study thus demonstrates that an established cooperative or competitive relationship is sufficient to modulate the degree of self-other integration on subsequent joint task performance. Importantly, by using Tetris, attention to others’ actions was beneficial both during cooperative and competitive game play and can thus not explain the competition-induced reduction of self-other integration.